The Use of Artificial Intelligence in Patient Experience in OP: A Review - Ramdurai, Balagopal (New Approaches in Engineering Research Vol. 10, 2021)
In the current years, due to the significant developments in technologies in almost every domain, the standard of living has been improved. Emergence of latest innovations, advanced machinery and equipment especially in the healthcare domain, have simplified the diagonalizing process to a wide extent. Smart techniques employed in medical applications resolved the detection and rectification of various diseases. This work involves analysing how usage of Artificial intelligence practice can improve patient experience across the gamut of the healthcare industry primarily in the Out Patient (OP) Segment. As per industry statistics 88% of the patients are willing to shift the healthcare provider without hesitation. A 2018 study by The Beryl Institute found that 91 percent of patients think patient experience is extremely or very important, and it has an impact on the healthcare decisions they make.